PENGARUH LATIHAN NAIK TURUN TANGGA TERHADAP KEMAMPUAN LONCAT KATAK PADA SISWA EKTRAKURIKULER OLAHRAGA CABANG ATLETIK - Jhony Hendra; Ikhsan Maulana Putra; Eko Haryono (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2022)
This research was motivated by the lack of frog jumping ability of students/athletes in the Kids' Athletics branch of the National Student Sports Competition (KOSN), causing achievement to be still low. The purpose of this study was to determine the effect of the up and down stairs training method on the ability to jump frogs in students who take part in extracurricular sports in athletics. The method in this research is quasi-experimental. The population of this research is all students who are members of extracurricular activities with a total of 193 students and the sample of this study is students who take part in extracurricular sports in the athletic branch totaling 11 people. The instrument used is a frog jumping ability test. The data analysis technique of this study used the t-test (t-test). The results of data analysis showed that there was a significant effect of the up and down stairs training method on the ability to jump frogs in students who took part in extracurricular sports in athletics. The results of the t-test obtained the value of sig. (2 tailed) of 0.01 < 0.05 then Ha: accepted and Ho: rejected. Based on the results of this study, it can be interpreted that the method of going up and down stairs has an influence on the frog's jumping ability. The method of going up and down stairs has a significant effect in this study after the percentage increase showed positive results, namely 18.05%. Through the results of this study, the method of going up and down stairs needs to be applied in coaching athletes to improve future achievements.